2021
DOI: 10.3390/ijms22116056
|View full text |Cite
|
Sign up to set email alerts
|

Structural Rearrangement of Dps-DNA Complex Caused by Divalent Mg and Fe Cations

Abstract: Two independent, complementary methods of structural analysis were used to elucidate the effect of divalent magnesium and iron cations on the structure of the protective Dps-DNA complex. Small-angle X-ray scattering (SAXS) and cryo-electron microscopy (cryo-EM) demonstrate that Mg2+ ions block the N-terminals of the Dps protein preventing its interaction with DNA. Non-interacting macromolecules of Dps and DNA remain in the solution in this case. The subsequent addition of the chelating agent (EDTA) leads to a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 43 publications
(67 reference statements)
0
6
0
Order By: Relevance
“…MsDps2 is a DNA-binding protein from Mycobacterium smegmatis starved cells, which protects its genome during hostile environmental conditions like starvation, oxidative stress, or antibiotic stress (Roy et al ., 2008, Saraswathi et al ., 2009). The structural insights of DNA binding motifs of Dps protein has been under investigation by many scientific groups (Tereshkin et al ., 2019, Dadinova et al ., 2021, Dubrovin et al ., 2021). Few studies utilized AFM and negative staining TEM to visualize the DNA-Dps complexes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MsDps2 is a DNA-binding protein from Mycobacterium smegmatis starved cells, which protects its genome during hostile environmental conditions like starvation, oxidative stress, or antibiotic stress (Roy et al ., 2008, Saraswathi et al ., 2009). The structural insights of DNA binding motifs of Dps protein has been under investigation by many scientific groups (Tereshkin et al ., 2019, Dadinova et al ., 2021, Dubrovin et al ., 2021). Few studies utilized AFM and negative staining TEM to visualize the DNA-Dps complexes.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies showed that Dps can form a 2D array in the presence of DNA which was imaged using cryoelectron tomography to characterize the 3D structure of the Dps-DNA complex. However, none of these studies could determine the atomic resolution structure of Dps molecules during the interaction with DNA (Tereshkin et al ., 2019, Dadinova et al ., 2021, Dubrovin et al ., 2021). In this study, we applied single particle cryo-EM to determine the high-resolution structures of the MsDps2-DNA complex.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two metabolites, d -glucoronate and d -galacturonate, have been shown to provoke the dissociation of Dps dodecamers [ 56 ]. Further, Mg 2+ ions (MgCl 2 ) block the interaction of the Dps N-terminals with DNA, while the addition of Fe 2+ (FeSO 4 ) provokes complex destruction and aggregation as well as the formation of iron-containing clusters in the central cavity next to the acidic pore [ 57 ].…”
Section: Bacterial Nucleoid-associated Proteins and Genome Protectionmentioning
confidence: 99%
“…Dps homologues with shorter, neutral, and/or spatially inaccessible N‐ or C‐terminal tails are generally unable to bind and compact DNA (Bozzi et al 1997 ; Papinutto et al 2002 ). The chemical composition of the solvent (namely pH, concentration of NaCl or Mg 2+ ) is a key factor in the regulation of the DNA binding process, that also affects the conformation of the N‐terminal tails (Huergo et al 2013 ; Lee et al 2015 ; Dadinova et al 2021 ; Soshinskaya et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%